Mediating Effect of Supply Chain Capabilities on the Relationship of Data Driven Supply Chain Management and Business Performance: A Study of the Manufacturing Industry - Tanasarn Panichayakorn (International Journal of Supply Chain Management, 2020)
Despite the data driven supply chain (DDSC) significance, the extant researches have a limited attention on how the DDSC effects to supply chain capabilities (SCC) to enhance the business performance (BP). Based on this gap, the main objective of the study is to investigate how DDSC effect to BP through the SCC in the manufacturing industries of the Indonesia. To achieve this objective, data has been collected from the 600 supply chain managers who were working in the food industry of Indonesia by using a simple random sampling technique which yield a 55% response rate. To analyze the results Smart PLS 3 software and structural equation modeling (SEM) was employed. The SEM findings has shown that in the direct effect DDSC has a significant and positive association with the BP, DDSC also have a significant and positive association with the SCC and SCC also has a positive and significant association with the BP. On the other hand, the indirect effect also shows that SCC is partially mediates in the relationship of DDSC and BP of the manufacturing industry of Indonesia. These findings show that SCC is considered to be a significant mediator in the relationship of DDSC and BP. Based on these findings, it could be considered that SCC is an important contribution which added a body of literature in the extant empirical studies. The findings of the current study could also be helped to supply chain managers to provide guideline to the supply chain mangers to know about the importance of the DDSC to increase the BP of the organization. The research limitations and future directions of the study also explained at the end of the study.